Application of Multi-terminal Pilot Protection Algorithm in Network Information Big Data for New Feeder Automation Terminal. Issue 1 (July 2021) - Zheng, Jianning
Abstract: With the development of big data and Internet of Things technology, society has put forward higher requirements for the safety and reliability of the power grid. In order to improve the overall power supply quality, the State Grid Corporation changed the previous concept of focusing on power transmission and light distribution, and increased its investment in the field of distribution network, which ushered in its own spring for the entire power distribution industry. This article aims to study the application of big data-based multi-terminal longitudinal directional protection algorithm in the new feeder automation terminal. Based on the introduction of the development status of feeder automation, the existing problems and the workflow of the multi-terminal longitudinal protection system, the multi-terminal longitudinal protection system is analyzed. The application of the directional protection algorithm in the feeder automation terminal. Finally, the treatment of abnormal situations is studied. The research results show that the new type of feeder automation terminal only needs to exchange the comprehensive information of the fault to independently detect and isolate the fault. This multi-terminal protection the structure has high flexibility and can quickly isolate faults, which can meet the protection requirements of the new feeder automation terminal.